2022
DOI: 10.17221/138/2020-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine or tramadol continuous rate infusions on the propofol requirements and cardiorespiratory variables in propofol-ketamine-midazolam anaesthetised cats

Abstract: The aim of this study was to compare the effects of midazolam-ketamine alone or in combination with dexmedetomidine or tramadol in a constant rate infusion (CRI) on the minimum infusion rate (MIR) of propofol and the cardiorespiratory function in cats undergoing an ovariohysterectomy (OH). This was a prospective, randomised, blinded clinical study. Twenty-four healthy female mixed-breed cats were premedicated with ketamine and midazolam. Propofol was used for the induction and maintenance of the anaesthesia (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…There are no pharmacokinetic studies in the veterinary literature on the use of tramadol for CRI in cats. Previous studies investigated its effects on inductive drug requirements and cardiorespiratory variables in anesthetized cats [ 16 , 26 , 56 ] and dogs [ 57 ]. Although it has been reported that tramadol is eliminated more slowly in cats than in dogs [ 22 ], further studies are needed to investigate the trend of plasma tramadol concentrations in cats.…”
Section: Discussionmentioning
confidence: 99%
“…There are no pharmacokinetic studies in the veterinary literature on the use of tramadol for CRI in cats. Previous studies investigated its effects on inductive drug requirements and cardiorespiratory variables in anesthetized cats [ 16 , 26 , 56 ] and dogs [ 57 ]. Although it has been reported that tramadol is eliminated more slowly in cats than in dogs [ 22 ], further studies are needed to investigate the trend of plasma tramadol concentrations in cats.…”
Section: Discussionmentioning
confidence: 99%